Late Neogene Chronostratigraphy, Biostratigraphy, Biochronology and Paleoclimatology. - Berggren,W. A.; Van Couvering,John (1973)
The integration of modern paleomagnetic, radiometric, and biostratigraphic studies has provided an accurate geochronological framework for the past 10 million years--the Late Neogene. Marine zones based on calcareous and siliceous planktonic organisms are recognized from the sub-Arctic region to the sub-Antarctic and their correlation to the paleomagnetic time scale is now feasible in some detail for the past 5 my. Likewise, the relationship of geochemically calibrated mammalian biochronology to the marine succession has been greatly improved. Within this framework of time it is possible to delineate the history of major features in Late Neogene paleontology, climatology, and oceanography. (Author) Prepared in cooperation with Brown Univ., Providence, R. I., and Colorado Univ. Museum, Boulder.